Substitusi Bungkil Kedelai dengan Tepung Daun Indigofera zollingeriana Terfermentasi terhadap Kinerja Produksi dan Glikogen Hati pada pemeliharaan ikan jelawat Leptobarbus hoevenii - Pangentasari, Dwinda; Setiawati, Mia; Priyo Utomo, Nur Bambang; Sunarno, Mas Tri Djoko; Harianto, Eko; Rolin, Febrina (Jurnal Akuakultur Sungai dan Danau, 2025)
Feed in aquaculture production is the largest production factor. Dependence on imported feed raw materials is the cause of high feed prices in fish farmers. One approach that can be done as a solution is the utilization of local raw materials, namely I. zollingeriana leaf flour fermented with sheep rumen fluid. This study aims to evaluate the use of fermented I. zollingeriana leaf meal (TDI) in feed as a substitute for soybean meal on the growth performance of catfish (L. hoevenii) fry. This study was conducted from December 2016 to June 2017. The research was conducted at the Wet Laboratory and Nutrition Laboratory of the Center for Freshwater Aquaculture Research and Fisheries Extension (BRBATPP), Bogor. This study consisted of four treatments and three replicates, namely the use of fermented amount of I. zollingeriana leaf meal (TDI) in feed as much as 0%, 10%, 20% and 30% made in isoprotein. The test fish used were jelawat fish that weighed 0.93 ± 0.02 g with a stocking density of 25 fish per aquarium. The container used was a 60x40x40 cm3 aquarium filled with water and equipped with 24-hour aeration. The results showed that the use of fermented I. zollingeriana leaf meal in feed up to 30% was significantly different from the control (0%) in several parameters including protein efficiency ratio, protein retention, fat retention, final weight, specific growth rate and feed efficiency, but not significantly different in the amount of feed consumption, hepatosomatic index and survival rate. The use of fermented I. zollingeriana leaf meal up to 20% showed results that were not significantly different from the control. Up to 20% fermented I. zollingeriana leaf meal can be used in tilapia (L. hoevenii) feed